Analysis of the Implementation of the National Industrial Information System (Siinas) at the Palembang City Industry Office - Mardisen, Devi; Hendarso, Yoyok; Lionardo, Andries (Electronic Journal of Education, Social Economics and Technology, 2025)
The presence of the digital era has indeed disrupted all aspects of life, including the policy sector. One of the uses of digital in current public policy is the existence of a national industrial information system (SIINas). SIINas is a mechanism to simplify and accelerate the process of delivering data from the business world to the government. The data is input which is then processed, analyzed, and used as a basis for the government in formulating a series of pro-industry policies, such as guaranteeing the availability of raw material and energy supplies, protection from the onslaught of imported goods, providing fiscal and non-fiscal facilities, and other policies. One of the agencies responsible for implementing SIINas is the Palembang City Industry Service which has a great responsibility for the presence of SIINas in the Palembang city area. Therefore, this study will analyze the implementation of SIINas at the Palembang City Industry Service, with the formulation of the problem which is related to what is the right form of implementation of the presence of SIINas and what are the factors that influence the success or obstacles in the Implementation of the National Industrial Information System SIINas at the Palembang City Industry Service. The results of this study indicate that the success of SIINas implementation is greatly influenced by a number of main factors, such as the suitability of policies to local needs, local government commitment, readiness of information technology infrastructure, quality of human resources, collaboration between stakeholders, and ongoing monitoring and evaluation. Then the second research result SIINas also faces a number of obstacles including limitations of IT infrastructure, lack of understanding and skills of human resources, resistance to change, budget constraints, lack of coordination between levels of government, and data security issues.